A study of vocabulary learning strategies among high and low Iranian English vocabulary learners - Rezvan Ghalebi; Firooz Sadighi; Mohammad Sadegh Bagheri (Cogent Education, 2021)
Learning a foreign/second language is a dynamic and complicated process that benefits from learners taking strategic steps to facilitate their own learning. Accordingly, the current study investigates the differences between Iranian high and low English vocabulary learners in terms of vocabulary learning strategies. Two hundred and eighteen university students in Iran took the vocabulary level test and filled out a vocabulary learning strategies survey. In fact, it was an attempt to examine if high/low learners differ significantly in using vocabulary learning strategies. To this end, 218 EFL, 111 high, and 107 low English vocabulary learners were selected to answer Schmitt’s Vocabulary Learning Strategies Questionnaire (VLSQ). The findings showed significant differences between high and low English vocabulary learners’ usage of determination, memory, cognitive, and metacognitive strategies. However, there was no significant difference in their use of social strategies.